Analyzing Prescient Factors for Satisfaction of High School Students Batam in English Subject Utilizing Hybrid Learning - Theodesia Lady Pratiwi; Feby Sintia Tan Surya (Institut Agama Islam Negeri Palopo, 2023)
Present research discusses student satisfaction with the English subject by using hybrid learning. This learning system is a learning adjustment process during Covid-19. High schools in Batam have implemented hybrid learning focusing on English subjects. This research aims to find out student satisfaction with hybrid learning by giving the predictive factor that has been provided and how students develop their English subject. The subjects of this research are 214 high school students in Batam, consisting of 20 schools. This study used a mixed method in which the data collection was done through questionnaires and interviews. This study provides factors in the form of satisfaction with hybrid learning, student's rate the computer literacy, student's perception toward the instructor and online learning, and the data from the questionnaire are strengthened by an interview result. The results showed that students rated computer literacy as the most satisfactory category, with an average of 4.33. Students' perceptions of teachers entered the category satisfied with an average score of 3.95, students' perceptions of online learning were also satisfied with an average score of 3.91, and students' attitudes towards hybrid learning were satisfied with an average value of 3.90. The interview results showed that each factor supported students in developing their English language learning. Each factor has advantages and disadvantages for developing English using hybrid learning.